Complications of Intravenous Tenecteplase Versus Alteplase for the Treatment of Acute Ischemic Stroke: A Systematic Review and Meta-Analysis. Issue 5 (23rd March 2023) - Rose, Deborah; Cavalier, Annie; Kam, Wayneho; Cantrell, Sarah; Lusk, Jay; Schrag, Matthew; Yaghi, Shadi; Stretz, Christoph; de Havenon, Adam; Saldanha, Ian J.; Wu, Teddy Y.; Ranta, Anna; et al.
Abstract : Background: Prior systematic reviews have compared the efficacy of intravenous tenecteplase and alteplase in acute ischemic stroke, assigning their relative complications as a secondary objective. The objective of the present study is to determine whether the risk of treatment complications differs between patients treated with either agent. Methods: We performed a systematic review including interventional studies and prospective and retrospective, observational studies enrolling adult patients treated with intravenous tenecteplase for ischemic stroke (both comparative and noncomparative with alteplase). We searched MEDLINE, Embase, the Cochrane Library, Web of Science, and the www.ClinicalTrials.gov registry from inception through June 3, 2022. The primary outcome was symptomatic intracranial hemorrhage, and secondary outcomes included any intracranial hemorrhage, angioedema, gastrointestinal hemorrhage, other extracranial hemorrhage, and mortality. We performed random effects meta-analyses where appropriate. Evidence was synthesized as relative risks, comparing risks in patients exposed to tenecteplase versus alteplase and absolute risks in patients treated with tenecteplase. Results: Of 2226 records identified, 25 full-text articles (reporting 26 studies of 7913 patients) were included. Sixteen studies included alteplase as a comparator, and 10 were noncomparative. The relative risk of symptomatic intracranial hemorrhage in patients treated with tenecteplase compared with alteplase in the 16 comparative studies was 0.89 ([95% CI, 0.65–1.23]; I 2 =0%). Among patients treated with low dose (<0.2 mg/kg; 4 studies), medium dose (0.2–0.39 mg/kg; 13 studies), and high dose (≥0.4 mg/kg; 3 studies) tenecteplase, the RRs of symptomatic intracranial hemorrhage were 0.78 ([95% CI, 0.22–2.82]; I 2 =0%), 0.77 ([95% CI, 0.53–1.14]; I 2 =0%), and 2.31 ([95% CI, 0.69–7.75]; I 2 =40%), respectively. The pooled risk of symptomatic intracranial hemorrhage in tenecteplase-treated patients, including comparative and noncomparative studies, was 0.99% ([95% CI, 0%–3.49%]; I 2 =0%, 7 studies), 1.69% ([95% CI, 1.14%–2.32%]; I 2 =1%, 23 studies), and 4.19% ([95% CI, 1.92%–7.11%]; I 2 =52%, 5 studies) within the low-, medium-, and high-dose groups. The risks of any intracranial hemorrhage, mortality, and other studied outcomes were comparable between the 2 agents. Conclusions: Across medium- and low-dose tiers, the risks of complications were generally comparable between those treated with tenecteplase versus alteplase for acute ischemic stroke.